هۆگری سۆزداری و په‌یوه‌ندی به‌ تێگه‌یشتنی خودی لای منداڵانی باخچه‌ له‌ دیدی دایكانه‌وه‌ - خان, پ.ی.د.هه‌ناو حسن محمد; محمد, كاژاو هادی (Sulaimani Journal for Humanities, 2023)
This study aims to determine the level of emotional interest in kindergarten children from the perspective of mothers and its relationship to the level of self-understanding. To achieve the objectives of the study and by using the descriptive approach, the researcher relied on developing a scale to measure each of the variables of emotional interest and self-concept, and after collecting data from (400) mothers of children of age, the results showed that both emotional attachment and self-concept there is no statistical difference in the level of emotional attachment According to the age variable (4 years-5 years), there was a statistical difference in the level of self-concept according to the age variable (4 years-5 years) , The relationship between emotional attachment and self-concept from the perspective of mothers of kindergarten children in Sulaymaniyah is a weak positive relationship.
Keywords: self concept; Emotional attachment